Revision of the Australian stiletto fly genus Acatopygia Kröber (Diptera: Therevidae: Agapophytinae) - Winterton, Shaun L. (Zootaxa, 2007)
The endemic Australian stiletto fly genus Acatopygia Kröber is revised. Acatopygia pulchella Kröber and Acatopygia paradoxa (Kröber) are redescribed and a neotype for A. paradoxa designated. A new species, Acatopygia olivacea sp. nov., is described and a key to Acatopygia species is presented.